An atlas of bloodstream-accessible bone marrow proteins for site-directed therapy of acute myeloid leukemia - Angenendt, Linus; Müller-Tidow, Carsten (Leukemia, 2018)
The concept of arming antibodies with bioactive payloads for a site-specific therapy of cancer has gained considerable interest in recent years. However, a successful antibody-based targeting approach critically relies on the availability of a tumor-associated target that is not only preferentially expressed in the tumor tissue but is also easily accessible for antibody therapeutics coming from the bloodstream. Here, we perfused the vasculature of healthy and acute myeloid leukemia (AML)-bearing rats with a reactive ester derivative of biotin and subsequently quantified the biotinylated proteins to identify AML-associated bone marrow (BM) antigens accessible from the bloodstream. In total, >1400 proteins were identified. Overall, 181 proteins were >100-fold overexpressed in AML as compared with normal BM. Eleven of the most differentially expressed proteins were further validated by immunohistochemistry and confocal microscopic analyses, including novel antigens highly expressed in AML cells (for example, adaptor-related protein complex 3 β2) and in the leukemia-modified extracellular matrix (ECM) (for example, collagen-VI-α-1). The presented atlas of targetable AML-associated BM proteins provides a valuable basis for the development of monoclonal antibodies that could be used as carriers for a site-specific pharmacodelivery of cytotoxic drugs, cytokines or radionuclides to the BM in AML.